Martin Luther King, Jr., and his birthday - Woodson, Jacqueline; Cooper, Floyd (Englewood Cliffs, NJ : Silver Press, 1990)
Describes the life of the civil rights worker who is honored on Martin Luther King Day.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Martin Luther King, Jr., Day -- Juvenile literature; African Americans -- Juvenile biography; Civil rights workers -- Juvenile literature; Clergy -- Juvenile literature